EDUKASI PERAN ORGANISASI PROFESI KEGURUAN BAGI MAHASISWA FKIP UNIVERSITAS MUHAMMADIYAH MAKASSAR SEBAGAI CALON PENDIDIK - Nur Inaya; Siti Nurjannah; Arviana Azzahra; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students of the Faculty of Teacher Training and Education (FKIP) at Universitas Muhammadiyah Makassar are future educators who play a vital role in educating the nation's life. However, situational analysis shows that student understanding regarding the aspects of legality and professional protection through teaching professional organizations is still very minimal. This community service aims to provide in-depth education regarding the roles, functions, and urgency of teaching professional organizations for students as a foundation for professionalism. The method of implementation is carried out through awareness-raising and increasing understanding of a problem using an educational literature review approach. The material covers the introduction of various professional organizations in Indonesia, such as PGRI and IGI, as well as the benefits of membership in providing legal protection and continuous competency development. The results of this activity indicate an increase in student awareness and enthusiasm in understanding their rights and obligations as members of the profession in the future. Through this education, it is expected that graduates of FKIP Unismuh Makassar will not only excel in pedagogical aspects but also be organizationally savvy in maintaining the dignity and honor of the teaching profession professionally and with integrity.